Revolução e contrarrevolução no cinema realista de Glauber Rocha. - Gabriel Caixeta de Paula Muller (2023)
The following thesis takes as its object the films Black god, white devil (1964) and Entranced earth (1967), trying to analyze how its style transforms brazilian populism's destruction and the subsequent counterrevolution into a critical representation of brazillian’s historic process of capitalist modernization. We understand that this representation is expressed allegorically, which means that we won’t be seeing the historical problems from early 1960 immediately in these works, but laid across a series of cinematic resources that organize and condense hard historical data from them, superposing different historical times. The present analysis tries to clarify some problems behind the representative style, trying to understand formal and theoretical parameters that build up the allegorical expression in our object, in such way, we deepen into readings about avant-garde cinema from the 40s to the 50s, brazilian popular-revolutionary art, Brecht's epic theater and Eisenstein intellectual cinema. We also make a historiographic reading, attempting a better understanding of historical questions allegorically expressed, like brazilian capitalist advancement, populism and it’s defeat, the regressive process that initiates in 1964, the armed fight against the military and it’s dictatorial state, the sertão’s economic reorganization in the old republic and the millenarist and the cangaço phenomena that occur in the same space and time.